Reproducibility of individual effect sizes in meta-analyses in psychology - Maassen, Esther; Van Assen, Marcel A.L.M.; Nuijten, Michèle B.; Olsson-Collentine, Anton; Wicherts, Jelte M. (Public Library of Science, 2020)
To determine the reproducibility of psychological meta-analyses, we investigated whether we could reproduce 500 primary study effect sizes drawn from 33 published meta-analyses based on the information given in the meta-analyses, and whether recomputations of primary study effect sizes altered the overall results of the meta-analysis. Results showed that almost half (k = 224) of all sampled primary effect sizes could not be reproduced based on the reported information in the meta-analysis, mostly because of incomplete or missing information on how effect sizes from primary studies were selected and computed. Overall, this led to small discrepancies in the computation of mean effect sizes, confidence intervals and heterogeneity estimates in 13 out of 33 meta-analyses. We provide recommendations to improve transparency in the reporting of the entire meta-analytic process, including the use of preregistration, data and workflow sharing, and explicit coding practices.
Keywords: General Biochemistry,Genetics and Molecular Biology; General Agricultural and Biological Sciences; General